Patronage, Power and Prowess: Barisan Nasional’s Equilibrium Dominance in East Malaysia - Faisal S. Hazis, (Kajian Malaysia, 2015)
Despite making significant inroads in Sabah and Sarawak during the 2013 elections, the Pakatan Rakyat (PR) party, with nine parliamentary seats, failed to weaken the Barisan Nasional (BN) party's control of these two East Malaysian states. The 47 seats won by the BN in Sabah and Sarawak accounted for 35% of the total number of seats (133) that it won nationally, indicating the importance of these East Malaysian states to the BN. Utilising a resource theory of single-party dominance, this chapter argues that the BN's electoral success in Sabah and Sarawak is dependent on the incumbent's use of patronage resources that are augmented by Prime Minister Najib Razak's seemingly limitless financial support. Equally important in explaining the BN's equilibrium dominance in East Malaysia is the role played by the Malay-Muslim bumiputera, who have emerged as the backbone of the ruling party. Fearing the loss of state power, the Malay-Muslim bumiputera consolidated behind the ruling party. The strong urban presence of the Chinese-dominated Democratic Action Party (DAP) further alienated Malay-Muslim bumiputera support for the PR. This chapter also explores the prowess of the BN's political machinery in gaining influence among the rural electorate scattered across the vast and rugged terrain of Borneo. Having made immense efforts to penetrate rural Sabah and Sarawak, the BN has established a strong presence there at the grassroots level that the opposition has yet to challenge. This chapter argues that unless the opposition can offer persuasive counter-narratives and party-building initiatives, the BN will continue to dominate politics in East Malaysia, ensuring its equilibrium dominance at the federal level.